The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.nurx.2006.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters and motor activity: Effects on functional recovery after brain injury

Abstract: Summary: There are complex relationships among behavioral experience, brain morphology, and functional recovery of an animal before and after brain injury. A large series of experimental studies have shown that exogenous manipulation of central neurotransmitter levels can directly affect plastic changes in the brain and can modulate the effects of experience and training. These complex relationships provide a formidable challenge for studies aimed at understanding neurotransmitter effects on the recovery proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…These body movements are present in the locomotor function of the rat [44] and may be qualitatively measured by the beam-walking test [30,45,46]. It has been documented that focal cortical damage in rats induces a temporary motor deficit [7,22,30,31,47]. The results of the present work revealed that cortical iron injection resulted in a motor deficit for 8 days.…”
Section: Figmentioning
confidence: 48%
See 2 more Smart Citations
“…These body movements are present in the locomotor function of the rat [44] and may be qualitatively measured by the beam-walking test [30,45,46]. It has been documented that focal cortical damage in rats induces a temporary motor deficit [7,22,30,31,47]. The results of the present work revealed that cortical iron injection resulted in a motor deficit for 8 days.…”
Section: Figmentioning
confidence: 48%
“…Our findings show that LP and motor deficit may indicate impaired neuronal connectivity in the corticospinal and CPC tracts resulting from cortical damage from iron in the cortex. Previously, it had been suggested that the noradrenergic system facilitates recovery in injured animals [6,7,22,32,47,48] because noradrenergic drugs facilitate motor recovery in injured rats [6,18,48]. However, evidence linking cerebellar 5-HT dysfunction to behavioral deficits remains scarce.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Other drugs affecting central neurotransmitters, when combined with training, may also modulate the recovery process. 20 Most clinical acute stroke trials, including ICTUS, do not control or account for the potential effects of poststroke physiotherapy or the use of other drugs that might affect functional recovery, and ICTUS did not require that a particular physiotherapeutic intervention be tied to drug administration.…”
Section: Strokementioning
confidence: 99%
“…Issues such as drug dose, timing of the intervention as well as its duration and intensity, patient comorbidity, and the location and extent of brain injury, among other factors, may be significant. 6,19,20 It is therefore not surprising that the results of small clinical trials of the effects of amphetamine on poststroke recovery in humans have been inconsistent, but mostly negative. 6 The Amphetamine Enhanced Stroke Recovery Trial, a National Institutes of Health-supported pilot clinical trial, is attempting to address some of the issues necessary for the design of a large prospective trial.…”
mentioning
confidence: 99%